2017
DOI: 10.1017/s1368980017000544
|View full text |Cite
|
Sign up to set email alerts
|

Stunting among children under 3 years of age in Côte d’Ivoire: spatial and temporal variations between 1994 and 2011

Abstract: In Côte d'Ivoire, significant changes in stunting prevalence were observed at the sub-national level between 1994 and 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Similar studies showed a slower decline of childhood stunting in Kenya and Côte d’Ivoire, where the prevalence of stunting decreased by 4·6 and 2·9 percentage points in the past two decades, respectively ( 6 , 27 ) . It is not clear whether transition from the NCHS/CDC reference to the WHO standards partially explains the minimal decreases in stunting in these countries.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar studies showed a slower decline of childhood stunting in Kenya and Côte d’Ivoire, where the prevalence of stunting decreased by 4·6 and 2·9 percentage points in the past two decades, respectively ( 6 , 27 ) . It is not clear whether transition from the NCHS/CDC reference to the WHO standards partially explains the minimal decreases in stunting in these countries.…”
Section: Discussionmentioning
confidence: 59%
“…According to our study, it appears that interventions implemented in the 1990s rather than 2000s may be responsible for most of the observed decease in stunting. Whether the stunting reduction mask related to transitioning between the NCHS/CDC reference and WHO growth standards observed in our study explains the minimal change in prevalence in stunting reported in other studies needs further investigation (27,33) .…”
Section: Discussionmentioning
confidence: 64%
“…7 Similarly, a study in Ivory Coast found that having an educated mother was protective against stunting in 3-year-old children. 55 In Bangladesh, Raihan et al 56 found that low SES (assets, maternal and household income and maternal education) increased the risk of wasting in children younger than 5 years of age. They also found that water sanitation and hygiene characteristics (e.g., use of soap, use of hygienic latrine and safe drinking water), often used as a composite of HWI and/or as a risk factor of infectious disease, mediated the association between SES factors and wasting.…”
Section: Socio-economic Factors and Infant Undernutrition Between Birmentioning
confidence: 99%
“…The UNICEF causal framework 3 has established that several immediate, underlying and basic causes play a role in infant undernutrition. Various combinations of causal factors were taken into account across the articles reviewed here, including infant gender, 55,60 infant feeding practices, 54,57 maternal age, 55 maternal anthropometry, 53 maternal morbidity (urinary tract infection, hypertensive disorders, malaria, human immunodeficiency virus, infection, gestational diabetes, pre-eclampsia, pregnancy induced hypertension, antepartum haemorrhage, pre-labour rupture of membranes, placental bleeding), 46 maternal obstetrical history (parity, previous PTB, gestation number), 46,48,67 access and usage of antenatal care services, household food insecurity, 55,60 household size and level of urbanisation. 54,60 Limitations This review has some limitations.…”
Section: Maternal and Household Ses Factors During The First 1000 Daysmentioning
confidence: 99%
“…Stunted growth has become the primary index for measuring malnutrition in children (UNICEF, 2009). Stunting is considered one of the optimal measures of long-term nutritional deficiencies and chronic malnutrition and is an indicator of poor socioeconomic environment for both mother and child (Barankanira et al, 2017). Stunted growth results from poor nutritional status and illness in a vital period for growth and development.…”
Section: Introductionmentioning
confidence: 99%